Post-Conflict Urban Heritage Reconstruction: The Case of Historic Mosul, Iraq - Rasheed, Chawan Osman M. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
During wars, historic towns have been systematically and deliberately destroyed. One of the main reasons for these systematic attacks is to make cities lose their identity and defeat citizens feeling of belonging. It is also the main reason motivating the related authorities to rebuild what has been lost during the conflict. The reconstructing process presents a different path in each example according to their special circumstances. This research discusses the post-conflict strategies for reconstructing the old city of Mosul, one of the oldest cities in the world, heavily destroyed during the rule of the Islamic State in 2014 and the liberation in 2017. Accordingly, this research used qualitative research methods throughout comparing and analyzing reconstructed cities and outlining their reconstruction methods. In the research, ten destroyed cities by war have been analyzed to examine different approaches regarding reconstruction to be implemented later in the old city of Mosul city. Then six cases have been studied in detail to direct the reconstruction process in Mosul. The cases are of Mostar, Coventry, Warsaw, Dresden, Beirut and Aleppo, that had been rebuilt or are still under reconstruction by different actors utilizing various methods. The selected cases are studied and analyzed in depth through research about their history, destruction, and rebuilding strategy. Each case gave us a different method and lesson that have been employed to propose strategies for rebuilding Mosul's old city. As a result, a paradigm has been presented considering the reconstruction facts and ground rules related to Mosul city. Keywords: Urban heritage, reconstruction, post-conflict, Mosul.

ÖZ: Savaşlar sırasında, kentsel miras genellikle sistematik ve kasıtlı olarak yok edilmektedir. Hedefli saldırıların ana sebeplerinden biri, insanlara, aidiyet duyguları yok olsun diye kimliklerinin hedef alındığını hissettirmektir. Savaşlar sırasında yok edilen veya tahrip edilen kentsel miras, aynı zamanda, yetkili kurum ve kişileri, kaybedilen değerleri yeniden inşa etmeye de motive eder. Yıkılmış, yok edilmiş kentsel mirası yeniden yapılandırma işlemi, her vakanın özel durumlarına göre her durumda farklı bir yol izlemeyi gerektirir. Bu araştırma, dünyanın en eski şehirlerinden biri olan ve IŞİD'in 2014'teki rolü ve 2017'deki kurtuluş sürecinde yıkılan eski Musul kentinin yeniden inşası için çatışma sonrası kentsel mirasın yeniden yapılandırılma stratejilerini ele almaktadır. Buna göre araştırma, öncelikle savaş sonrası yeniden inşa edilmiş olan benzer kentleri karşılaştırmalı olarak analiz etmiş ve yeniden inşa yöntemlerini nitel araştırma yöntemlerini kullanarak incelemiştir. Bu araştırmada, öncelikle dünyanın farklı coğrafyalarında savaş nedeniyle yok edilen 10 farklı kent çalışılmış ve daha sonra Musul şehri ile karşılaştırıp ve 6 kent - Mostar, Coventry, Warsaw, Dresden, Beirut and Aleppo - seçilerek ayrıntılı olarak analiz edilmiştir. Söz konusu örnekler, tarihsel geçmişleri, savaş dolayısıyla yıkımları ve yeniden inşa stratejileri bağlamında incelenmiştir. Bu karşılaştırmalı incelemelerden edinilen öğretiler, araştırmanın asıl vakası olan Musul'un eski kent dokusunu yeniden inşa etmek için stratejiler önermek için kullanılmıştır. Sonuç olarak, Musul kentine özgü yeniden yapılanma gerçekleri ve temel kurallar göz önünde bulundurularak bir paradigma sunulmuştur. Anahtar Kelimeler: Kentsel miras, çatışma sonrası yeniden inşaat, Musul
Master of Science in Urban Design. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2021. Supervisor: Prof. Dr. Şebnem Önal Hoşkara.
Keywords: Architecture; Urban Design; Historic sites--Conservation and restoration; Historic Buildings--Preservation--Mosul (Iraq); Cultural property--Protection; Historic preservation; Urban heritage; reconstruction; post-conflict; Mosul; Urban Planning